Process management and improvement in health services: a hospital appointment system example - TUNCALI YAMAN, TUTKU (My University, 2023)
In today’s competitive conditions, businesses that produce goods or services frequently benefit from process improvement and similar methods to achieve their goals. Being process-oriented means giving importance to the creation of quality, not quality control. The Hospital Appointment system is the admission of patients to polyclinics at certain time periods. The purpose of the appointment system for the patients is to organize and spread the time of the patients’ arrival at the hospital outpatient clinics. In general, to solve the waiting problem in hospitals, health services are provided by distributing patients to certain time periods. However, due to the insufficient capacity of the hospital, the patients’ demand for health services cannot be met, and therefore the appointment problem continues. Patients spend days on the internet and on the phone to get an appointment from some medical units. In this context, the aim of the study is to evaluate the problems experienced in the appointment process in health services in terms of quality, time, technique and customer satisfaction, to make improvements and evaluate results.
Keywords: Appointment System; Health Services; Process Improvement